Analisis Transparansi, Akuntabilitas dan Pemanfaatan Teknologi Informasi dalam Pengelolaan Dana Desa - Putri Nabila; Vita Fitria Sari (Universitas Negeri Padang, 2024)
The aim of this research is to determine transparency, accountability and the use of information technology in managing village funds in villages in Tanah Kampung District. This study uses a quantitative approach. The type of research applied is descriptive research. The difference between this research and previous research is the addition of a variable, namely the use of information technology. The next difference is in the intended respondents. Another difference is that the previous research used associative quantitative research while this research uses descriptive quantitative research. The research results show that: 1) Village fund management in villages in Tanah Kampung District is not yet fully transparent. 2) Village fund management in villages in Tanah Kampung District is not yet fully accountable. 3) village fund management in villages in Tanah Kampung District has not fully utilized technological information. Recommendations for future research are to include the community as respondents in the research.